2004
DOI: 10.1111/j.1067-1927.2004.012505.x
|View full text |Cite
|
Sign up to set email alerts
|

Histologic evaluation of skin‐derived and collagen‐based substrates implanted in palatal wounds

Abstract: Tissue shortage complicates the surgery of cleft lip and palate anomalies and the healing of defects on the palate impairs growth of the dento-alveolar complex due to scar tissue formation. Implantation of substitutes into the wound area might overcome this adverse effect. The aim of this study was to compare the tissue response to three collagen-based (collagen type I substrate alone, or collagen coated with elastin or chondroitin-6-sulfate) and two skin-derived substrates (unprocessed dermis and AlloDerm) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 54 publications
1
25
0
3
Order By: Relevance
“…We only found a transient influx of myofibroblasts between 1 and 2 weeks, including those of the sham groups, which is in accordance with a study on collagen scaffolds implanted in the palate of dogs. 47 Myofibroblasts are related to both wound contraction and scar formation. 48,49 In palatal wounds of rats, myofibroblasts are mainly present between 4 and 22 days, with a peak intensity after 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…We only found a transient influx of myofibroblasts between 1 and 2 weeks, including those of the sham groups, which is in accordance with a study on collagen scaffolds implanted in the palate of dogs. 47 Myofibroblasts are related to both wound contraction and scar formation. 48,49 In palatal wounds of rats, myofibroblasts are mainly present between 4 and 22 days, with a peak intensity after 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…Ophof et al reported fewer histologic indications of scar tissue formation in open palatal wounds in beagle dogs grafted with various dermal substrates. 42 Reducing scar formation and wound contracture may help to decrease the incidence of oronasal fistulas and to reduce palatal shortening and its associated functional deficits. In 2003, Clark et al 43 reported their experience with human acellular dermal matrices in treating six cleft palate patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, picrosirius stained histological slices have been examined under bright field illumination. The quantification of collagen in picrosirius stained slices using bright field has been described elsewhere [38][44]. For each animal, a mean value was derived from the analysis of 9 histological slices.…”
Section: Methodsmentioning
confidence: 99%